Does occupational licensing impact incomes? - The German crafts case - Kaja Fredriksen (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2018)
The empirical literature on occupational licensing finds standard monopoly effects of entry regulations: Less competition and economic rents for professionals. I exploit the natural experimental design of a change in the German crafts regulation in 2004, which removed the traditional licensing requirement only for certain trades, and find no robust effects. I point out that existing studies on the income effects of occupational licensing suffer from methodological weaknesses. Most studies rely on cross-section estimates that are likely to be biased due to unobserved heterogeneity whereas others do not rigorously define the population of interest. Based on my results, I suggest that demand-effects and market saturation have so far been inadequately discussed in the literature.
Keywords: I28; I39; J24; L51; 330; Labor markets; occupational licensing; monopoly rent; natural experiment; craftsmanship